Dysproporcje dochodów budżetowych w wybranych powiatach ziemskich i próby ich wyrównywania w Polsce - Rudowicz, Emil (Disproportions of Fiscal Income in Selected Terrestrial Poviats and The Attempt of its Equalization, 2009)
The paper presents an analysis of financial situation of territorial self-government chosen in a conscious way in the aspect of the income structure and performing disproportions. The article also shows the equalizing solutions applied by the legislator concerning the general subsidy and expedient subsidies directed to the committee sector units. The article focuses only on the selected economic factors that influence the disproportions in the average level units of territorial government
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 277-287